2006
DOI: 10.1097/00002820-200609000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Hope and Related Variables in Italian Cancer Patients

Abstract: Hope, long considered an essential element for life, has been shown to be important among cancer patients in coping, perceived control over the illness, and psychologic adjustment to the illness. The purpose of this study was (a) to describe the level of hope in Italian cancer patients; (b) to compare the levels of hope during and after hospitalization; (c) to determine whether hope was correlated with quality of life and several symptoms; and (d) to determine whether the variables from the international liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
89
0
9

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(110 citation statements)
references
References 43 publications
9
89
0
9
Order By: Relevance
“…In line with the findings of this study, Fadıoğlu et al (2006), in their study conducted with breast cancer patients, and Vellone et al (2006) and Aslan et al (2007), in their study conducted with cancer patients, found no significant relationship between hope and the duration of the illness. However, due to its long treatment process and considerable side effects, breast cancer is an illness which requires a lot of energy.…”
Section: Discussionsupporting
confidence: 86%
“…In line with the findings of this study, Fadıoğlu et al (2006), in their study conducted with breast cancer patients, and Vellone et al (2006) and Aslan et al (2007), in their study conducted with cancer patients, found no significant relationship between hope and the duration of the illness. However, due to its long treatment process and considerable side effects, breast cancer is an illness which requires a lot of energy.…”
Section: Discussionsupporting
confidence: 86%
“…There are some studies showing that as patient social support levels increase, so do their hope levels. [32][33][34] Unlike these studies, Fadiloğlu et al (2006) conducted a study of the relationship between hopelessness levels of women with breast cancer and their coping behaviors and determined that social support had no effect on levels of hopelessness. [35] The present study found a very slight correlation between multidimensional perceived social support scores and hope scores, although both are above moderate level.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies about the hope levels of patients with various cancer types indicate that the patients have high hope levels (Vellone et al, 2006;Felder, 2004;Abdullah-zadeh, Agahosseini, AsvadiKermani & Rahmani, 2011). Results of the present study are thus parallel to the literature.…”
Section: Discussionmentioning
confidence: 99%